2018
DOI: 10.1039/c8nr00914g
|View full text |Cite
|
Sign up to set email alerts
|

A lead-free two-dimensional perovskite for a high-performance flexible photoconductor and a light-stimulated synaptic device

Abstract: Organo-lead halide perovskites have emerged as promising materials for high-performance photodetectors. However, the toxicity of lead cations in these materials limits their further applications. Here, a flexible photoconductor is developed based on lead-free two-dimensional (2D) perovskite (PEA)2SnI4via a one-step solution processing method. The flexible transparent electrodes are patterned from rGO/(PEDOT:PSS) hybrid films. The stability and reproducibility of the devices are significantly improved on adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
155
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(159 citation statements)
references
References 42 publications
4
155
0
Order By: Relevance
“…Since the carrier mobility of MAPbI 3 is very close to that of FASnI 3 , the much higher responsivity cannot be correlated to the difference in the mobilities of the two materials. [13,19,28,29] Actually, high gain PDs enabled by selective trapping of photocarriers at defect states were reported before for other materials. We consider that the low photoresponse of the MAPbI 3 device is attributed to the trapping of both photogenerated electrons and holes in the perovskite layer by crystal defects and grain boundaries.…”
Section: Doi: 101002/advs201900751mentioning
confidence: 80%
See 2 more Smart Citations
“…Since the carrier mobility of MAPbI 3 is very close to that of FASnI 3 , the much higher responsivity cannot be correlated to the difference in the mobilities of the two materials. [13,19,28,29] Actually, high gain PDs enabled by selective trapping of photocarriers at defect states were reported before for other materials. We consider that the low photoresponse of the MAPbI 3 device is attributed to the trapping of both photogenerated electrons and holes in the perovskite layer by crystal defects and grain boundaries.…”
Section: Doi: 101002/advs201900751mentioning
confidence: 80%
“…[22] Although much higher responsivity and gain can be achieved in PDs by introducing heterostructures in the devices, [22][23][24][25] the additional processing steps and materials involved in the devices may complicate the fabrication procedure and increase the cost. [27][28][29][30][31] For instance, Waleed et al fabricated a MASnI 3 nanowire-array PD by using a vapor phase chemical reaction method with porous alumina template, exhibiting a responsivity and detectivity of only 0.47 A W −1 and 8.80 × 10 10 Jones, respectively. [26] In light of this, some works have been done on lead-free perovskite-based PDs, yet satisfactory results are still lacking.…”
Section: Doi: 101002/advs201900751mentioning
confidence: 99%
See 1 more Smart Citation
“…Although MAPbI 3 ‐based photonic synapses demonstrate excellent performance, lead element in MAPbI 3 is highly toxic and it can easily pollute the environment, so that it is an enormous demand to design green devices based on lead‐free perovskites. Recently, Qian et al first fabricated a flexible photonic synaptic device based on (PEA) 2 SnI 4 , which is one kind air‐stable lead‐free 2D perovskite . The perovskite film is developed through one‐step solution approach and rGO/(PEDOT:PSS) is worked as the flexible electrode.…”
Section: Emerging Materials‐based Synaptic Devicesmentioning
confidence: 99%
“…The usage of perovskites in data storage have attracted huge amounts of interests and a number of memory devices based on inorganic or hybrid organic–inorganic perovskites (HOIP) with superior electrical performances have been investigated. Especially, because of the intense light‐harvesting property as well as significant hysteresis, perovskite materials were widely utilized to fabricate photo‐responsive memory devices, including light tunable flash memory and ReRAM . For instance, Chen et al reported a flash memory based on CH 3 NH 3 PbBr 3 (MAPbBr 3 ) displaying multilevel memory behavior by applying light illumination .…”
Section: Photo‐tunable Memorymentioning
confidence: 99%